An Analysis of Theme Progression in Wiliam Blake’s “Infant Joy” - Muhammad Alvin Firmansyah; Bilqisth Permata Sahara; Irma Khoirot Daulay; Toyyibah Toyyibah (Journal on Education, 2024)
This research investigates the realisation of any types of themes in William Blake’s poetry in which entitled Infant Joy. This study has analyzed the poem by studying the themes and rhemes then identifying each role of every themes. It is found that all types of themes in which are topical, interpersonal, and textual, are appeared in this poetry. There are five topical themes, four interpersonal themes and two textual themes. Making this poem is rich with the expression of happiness, affection, and well-wishing, showing a deep, intimate bond between the speaker and the child.